SPE Asia Pacific Oil and Gas Conference and Exhibition 2001
DOI: 10.2118/68723-ms
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanism of Polymer Solution With Visco-Elastic Behavior Increasing Microscopic Oil Displacement Efficiency and the Forming of Steady "Oil Thread" Flow Channels

Abstract: In this paper, the visco-elastic characteristics of polyacrylamide solution have been studied experimentally. The mechanisms of the effect of polymer solution with visco-elastic characteristic on each type of residual oil after water flooding are analyzed and the mechanisms of polymer solution with visco-elastic characteristic increasing microscopic oil displacement efficiency are studied. By the analysis of microscopic experiments of percolating flow, corresponding relationships between the characteristic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(32 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…Currently, polymer flooding is considered as one of the most promising technologies in EOR process because of its technical and commercial feasibility. Particularly, the interest on polymer flooding applications worldwide has been stimulated by the outstanding results reported from the large-scale polymer flooding application in the Daqing oil field in China, with incremental oil productions of up to 300,000 barrels per day [47].…”
Section: Polymermentioning
confidence: 99%
“…Currently, polymer flooding is considered as one of the most promising technologies in EOR process because of its technical and commercial feasibility. Particularly, the interest on polymer flooding applications worldwide has been stimulated by the outstanding results reported from the large-scale polymer flooding application in the Daqing oil field in China, with incremental oil productions of up to 300,000 barrels per day [47].…”
Section: Polymermentioning
confidence: 99%
“…However, for conditions associated with the Daqing reservoir, researchers (Wang et al 2000, 2001a, 2001b, Xia et al 2004, Wu et al 2007) argued that HPAM solutions reduced S or by 6 to 15 saturation percentage points, even with waterfloods and polymer floods conducted at the same constant capillary number. Notably, Wu et al (2007) observed that HPAM polymers reduced the waterflood S or by up to 15 saturation percentage points (i.e., a S or of 36.8% with waterflooding versus 21.75% for polymer flooding) using a constant capillary number of 5x10 -5…”
Section: Previous Literaturementioning
confidence: 99%
“…138 Furthermore, they impart greater solution viscoelasticity, which provides higher oil recoveries and lower residual oil saturations under Daqing conditions. 139 From the two pilot tests 140 at Daqing (specifically, at areas called "West of Center" and "4-4# Station of the Northwest in Lamadian"), the following observations were noted: (1) Water intake profile was improved after injecting higher polymer concentrations. (2) During polymer flooding, the period of relatively low water cuts can be prolonged by injecting higher polymer concentrations.…”
Section: More Viscous Polymer Solutionsmentioning
confidence: 99%